2015
DOI: 10.1016/j.lisr.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of affect in studies of information behavior in HIV/AIDS contexts: An exploratory quantitative content analysis

Abstract: Information seeking and use are critically important for people living with HIV/AIDS, and for those who care for people with HIV/AIDS. In addition, the HIV/AIDS context is characterized by significant affective or emotional aspects, including stigma, fear, and coping. Thus, studies of information behavior in this context should be expected to take account of emotional variables.In information behavior scholarship, emotional variables have been marginalized in favor of a focus on cognitive aspects, although in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…Similar to this study, a review conducted in Africa found that patients want a better understanding of their medications and that stigma may prevent access to information (Patel & Dowse, 2013). Other studies pertaining to HIV also found that information regarding healthy lifestyles, emotional health, or general wellness issues would be useful to patients (Anderson et al, 2012; Huber & Cruz, 2000; Julien & Fourie, 2015). Across the international literature, patients identified different sources of information but generally indicated that providers are either the best sources or one of the biggest barriers to effective information exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, a review conducted in Africa found that patients want a better understanding of their medications and that stigma may prevent access to information (Patel & Dowse, 2013). Other studies pertaining to HIV also found that information regarding healthy lifestyles, emotional health, or general wellness issues would be useful to patients (Anderson et al, 2012; Huber & Cruz, 2000; Julien & Fourie, 2015). Across the international literature, patients identified different sources of information but generally indicated that providers are either the best sources or one of the biggest barriers to effective information exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these barriers may include: lack of educational infrastructure, limited financial resources, unavailability of information, cultural differences between patients and providers, spiritual beliefs, and transportation restrictions [14, 16, 17]. In the context of HIV, information seeking and use is further complicated by negative emotional responses to a positive diagnosis and widespread stigma, among other psychosocial factors [1, 7, 1820]. Despite the importance of information in the battle against HIV, studies pertaining to health information seeking, processing, and use are missing from many regions.…”
Section: Introductionmentioning
confidence: 99%
“…Principals do not receive sufficient support or training to cope with the problems they are facing (Buchel and Hoberg, 2007;Aggleton et al, 2011). Because HIV affects not only the physical well-being of the organisation, but also its psychological health, it is the most complicated epidemic with which to deal (Julien and Fourie, 2015). As Van Dyk and Van Dyk (2012, p.464) emphasise, one of the consequences of an unhealthy workforce is "low staff morale with employees resenting taking on or refusing to take on additional responsibilities for colleagues who are sick".…”
Section: Leading Schools In Sensitive Mattersmentioning
confidence: 99%